Kualitas Pelayanan Gigi dan Mulut di Puskesmas Tamalate: Menggali Tingkat Kepuasan Pasien Untuk Perbaikan Berkelanjutan - Pariati; Wijaya, Ayu; Adam, Andi Muhammad; Rahmadani, Nanang; Zulkarnain (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2024)
Patient satisfaction with the quality of dental and oral health services is a comparison between perceptions of the services received and expectations before receiving services. Service quality is the service activities provided by service providers that are able to fulfill expectations, desires, and needs and are able to provide satisfaction to the wider community. This research was carried out at the Tamalate District Health Center. Tamalate Makassar is based on five dimensions of service quality, namely tangible form, reliability, responsiveness, assurance, and empathy based on a Likert scale. The aim of this research is to determine the quality of dental and oral health services at the Tamalate Community Health Center. The type of research is descriptive with a sample size of 30 people. The sampling method uses a purposive sampling method. The research results showed that 44% of patients were satisfied with the dimensions of the real form. In the reliability dimension, it shows 57% satisfaction. The responsiveness dimension shows 47% satisfaction. In the assurance dimension, 50% were very satisfied and in the empathy dimension, 47% were satisfied.